'It's nice to be appreciated': Understanding heterosexual men's engagements with sexting and sharing Dick Pics. (March 2022) - Waling, Andrea; Kerr, Lucille; Bourne, Adam; Power, Jennifer; Kehler, Michael
This paper explores heterosexual men's experiences of sexting with a primary focus on how, when and why men send sexually explicit photos to women. Previous research has focused either on gay and bisexual men's experiences or considered sexting within a broader youth context. This research considers young men and their engagement with sexting practices and its relationship to how they view and understand their bodies as desirable and sexual. Drawing from work that has called for more reflexive considerations of men's emotions and sexuality, we explore the processes by which men engage in the practice of sexting (how/where they take photos), the affects that sexting provides (how it makes them feel), their rationale for engaging in the practice (why they do it) and their expectations from partners (e.g. reciprocal photos, partner's responses). The findings of this paper suggest that while men highlight a range of affects and experiences with sexting, on the whole, it helps boost sexual confidence with partners and create and sustain intimacy, particularly in between seeing (in person) a partner or partners. Our research further suggests that men share similar concerns to women in other studies who are concerned about their photos becoming public, thus revealing a primary reason why this particular population of heterosexual men may not engage in the sending of erotic photos.